2005
DOI: 10.1046/j.1365-2842.1997.00485.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pulsed electromagnetic fields on maturation of regenerate bone in a rabbit limb lengthening model

Abstract: ABSTRACT:To study the effect of applying pulsed electromagnetic fields (PEMF) during the consolidation phase of limb lengthening, a mid-tibial osteotomy was performed in 18 adult New Zealand White rabbits and an external fixator was applied anteromedially. Animals were randomly assigned to treatment and control groups. After a 7-day latency period, the tibiae were distracted 0.5 mm every 12 h for 10 days. The treatment group received a 20-day course of PEMF for 60 min daily, coinciding with initiation of the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 38 publications
1
9
0
4
Order By: Relevance
“…There was a small but significant tendency for the signs and symptoms to be more prevalent among girls. An Italian study [24] examined 240 boys and girls aged 7 to 16 years. Although signs and symptoms of TMDs were fairly common, they were mild in most instances.…”
Section: Childrenmentioning
confidence: 99%
“…There was a small but significant tendency for the signs and symptoms to be more prevalent among girls. An Italian study [24] examined 240 boys and girls aged 7 to 16 years. Although signs and symptoms of TMDs were fairly common, they were mild in most instances.…”
Section: Childrenmentioning
confidence: 99%
“…16 , 17 , 21 Despite these results, there are studies that indicate different types of malocclusions have a significant effect on TMDs. 16 , 20 Except lip and nail biting and resting the head on the hand as parafunctional habits, clenching, premature contacts during protrusive movements, and bruxism had a significant association with TMDs. The relationship between parafunctional habits and TMDs was also demonstrated previously, 19 although several studies found no such relationship.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between parafunctional habits and TMDs was also demonstrated previously, 19 although several studies found no such relationship. 16, 21, 24, 29, 30 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Barone et al (14) y Tuerling et al (15), también mencionan al chasquido articular como el síntoma más común de los TTM, seguido por el patrón alterado de apertura/cierre mandibular (14). Zanandréa et al mencionan al dolor muscular y articular como síntomas primarios, y en segundo término al chasquido a la apertura/cierre junto con otros ruidos articulares (16).…”
Section: Signos Y Síntomas Ttmunclassified